AUS Predicts Residual Nodal Disease after NAC - Buckley, Rita (MD Conference Express, 2015)
Axillary ultrasound (after neoadjuvant chemo-therapy can help to restage axillary nodal basins for patients with clinical node-positive (cN1) breast cancer, sparing many from the morbidity associated with axillary lymph node dissection. This article reports on the results of a secondary end point of the American College of Surgeons Oncology Group (ACOSOG) Z1071 trial.